2007
DOI: 10.1111/j.1439-0426.2007.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of shovelnose sturgeon and pallid sturgeon in the free-flowing Mississippi River

Abstract: Gut contents of shovelnose and pallid sturgeon from the lower and middle Mississippi River were obtained by colonic flushing, a safe and easily implemented alternative to gastric lavage. Diets of both species were dominated numerically by immature Trichoptera, Ephemeroptera, and Diptera. Primary prey, based on volume, for shovelnose sturgeon were Trichoptera, and for pallid sturgeon were various fishes. Geographic and seasonal nuances in diet were observed for both species, but the general dichotomy of shoveln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 10 publications
8
56
0
Order By: Relevance
“…1 A stretch of riverine habitat in Ft. Loudoun Reservoir, Tennessee on the Tennessee River, which is known to reliably harbor lake sturgeon (Acipenser fulvescnes) (Saidak 2015); cross hatches symbolize the entirety of the study area and into the colon. This method was developed successfully for pallid sturgeon (Scaphirhynchus albus) and shovelnose sturgeon (S. platorynchus) in the Mississippi River by Hoover et al (2007). The bottle is gently squeezed in short pulses, and feces expelled into a dissecting pan.…”
Section: Lake Sturgeon Samplingmentioning
confidence: 99%
“…1 A stretch of riverine habitat in Ft. Loudoun Reservoir, Tennessee on the Tennessee River, which is known to reliably harbor lake sturgeon (Acipenser fulvescnes) (Saidak 2015); cross hatches symbolize the entirety of the study area and into the colon. This method was developed successfully for pallid sturgeon (Scaphirhynchus albus) and shovelnose sturgeon (S. platorynchus) in the Mississippi River by Hoover et al (2007). The bottle is gently squeezed in short pulses, and feces expelled into a dissecting pan.…”
Section: Lake Sturgeon Samplingmentioning
confidence: 99%
“… A comparison of food habitats for the shovelnose ( Scaphirhynchus platorynchus ) and pallid ( S. albus ) sturgeon from the Mississippi River (Hoover et al., 2007) with the results of this study for the Alabama sturgeon …”
Section: Discussionmentioning
confidence: 93%
“…Shovelnose sturgeon feed principally on aquatic insects (e.g. Gerrity et al., 2006; Hoover et al., 2007), while the pallid sturgeon feeds on aquatic insects and fishes (e.g. Gerrity et al., 2006; Hoover et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the Cyprinidae family was most represented by Macrhybopsis but the level of digestion generally prohibited further identification. Finally, Hoover et al (2007) found that pallid sturgeon in the middle Mississippi River consumed Cyprinidae, Sciaenidae, and Clupeidae.…”
mentioning
confidence: 99%